2013
DOI: 10.1155/2013/341606
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Functional Lower Urinary Tract Dysfunction in Children: Are the Physicians Complying with the Current Guidelines?

Abstract: Objective. To elucidate whether the diagnostic and treatment approaches of the physicians for functional lower urinary tract dysfunction (LUTD) in children is complying with the current guidelines. Material and Methods. We have conducted an internet-based national survey for the physicians from different departments randomly sampled from the database of Turkish Paediatric Urology Society. Participants were asked to answer two-page questionnaire consisting of 4 main sections: “demography,” “working conditions,”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Additionally, studies have shown that urotherapy reduces the need for surgery in patients with VUR and decreases constipation and the number of urinary tract infections ( 15 ). In addition, several authors reported that in many studies without biofeedback, successful results were obtained with standard urotherapy ( 14 , 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown that urotherapy reduces the need for surgery in patients with VUR and decreases constipation and the number of urinary tract infections ( 15 ). In addition, several authors reported that in many studies without biofeedback, successful results were obtained with standard urotherapy ( 14 , 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same document states that patient‐reported outcomes (PRO) constitute the greatest source of information on the impact of symptoms and the treatment benefit from the patient's perspective. The bladder diary (BD) is the most commonly used instrument to evaluate UI and “urgency” in clinical trials, although it is rarely used in the regular practice of urologists, and not used at all by primary care physicians, even although its use is recommended in the initial evaluation of patients with UI by the guidelines of the European Association of Urology as a semi‐objective measurement of evaluation for LUTS. According to a recent review of the published studies focused on the development and validation of different BD in terms of format, contents and duration, none of them fulfill the standards established to be regarded valid.…”
Section: Introductionmentioning
confidence: 99%
“…12 Paediatricians, who are the first to see young patients in the medical system, may be best positioned to identify and provide this type of treatment. However, only onefourth of urologists and nephrologists indicated they followed standard guidelines, 13 and even less is known about paediatricians. Questionnaire-based assessments of healthcare providers worldwide have demonstrated insufficient knowledge to meet guideline-recommended care.…”
Section: What This Study Addsmentioning
confidence: 99%